2022
DOI: 10.3390/diagnostics12010131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Oncuria™, a Multiplexed Liquid Biopsy for the Non-Invasive Detection of Bladder Cancer—A Pilot Study

Abstract: Oncuria™ is a validated quantitative multiplex immunoassay capable of detecting bladder cancer from a voided urine sample. Herein, we sought to determine whether Oncuria™ affects physicians’ use of non-invasive and invasive diagnostic tests for microhematuria, gross hematuria, and bladder cancer surveillance. We conducted a survey-based study to assess physician management of nine clinical scenarios involving real-world data from patients with gross hematuria, microhematuria, and bladder cancer on surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Sequential Cxb tests stratify patients with a low or high probability of HIT with a 4.8-fold higher diagnostic yield than stratification according to the American Urological Association guidelines. Oncuria™ [ 36 , 37 ] has proven to be a test that can rule out the presence of BCa, reduce healthcare costs and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential Cxb tests stratify patients with a low or high probability of HIT with a 4.8-fold higher diagnostic yield than stratification according to the American Urological Association guidelines. Oncuria™ [ 36 , 37 ] has proven to be a test that can rule out the presence of BCa, reduce healthcare costs and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot survey study [ 37 ] using Oncuria™ investigated how the test affects physicians’ use of non-invasive and invasive diagnostic tests for microhaematuria, gross haematuria, and BCa surveillance. The results showed that with a negative test result, the total number of diagnostic procedures was reduced by 31% and a positive result by 27%.…”
Section: What Is New In the Last Two Years?mentioning
confidence: 99%
“…Most, if not all, FDA-approved urine tests have also yielded inconsistent results and/or suboptimal efficacy. Although some urine-based biomarkers have shown sensitivity comparable to cystoscopy, they have not been tested in multicenter studies or randomized clinical trials [ 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ].…”
Section: Urine Biomarkers For Bc: Clinical Need and Realitymentioning
confidence: 99%
“…Along with the advancement of multiplex assays, the current emphasis is on the simultaneous assaying of multiple biomarkers to achieve better diagnostic ability. ONCURIA is a multiplexed bead immunoassay that measures angiogenin (ANG), apolipoprotein E (APOE), alpha-1 antitrypsin (A1AT), carbonic anhydrase 9 (CA9), interleukin-8 (IL-8), matrix metallopeptidase 9 (MMP9), matrix metallopeptidase 10 (MMP10), plasminogen activator inhibitor 1 (PAI1), syndecan 1 (SDC1), and vascular endothelial growth factor (VEGF) levels in urine and creates a validated signature to diagnose BC [ 209 ]. In prospective studies, the test has shown 90% or more sensitivity; furthermore, false positive results due to whole blood were shown to be negated by centrifugation of the samples [ 209 , 222 , 223 , 224 ].…”
Section: Ease Of Developing Urine Biomarkersmentioning
confidence: 99%
“…5 Oncuria® (Nonagen Bioscience Corporation, Los Angeles, CA) is a bead-based multiplex uorescence immunoassay that coordinately measures 10 protein biomarkers in urine samples. [12][13][14][15] Biomarker levels are converted into composite risk scores using differently-weighted algorithms tailored for either assisting BC diagnosis, predicting response to BCG therapy in early-stage intermediate to high-risk disease, or tracking treatment progress. The assay is CE marked in Europe and was assigned FDA Breakthrough Device status for expedited review in the USA.…”
Section: Introductionmentioning
confidence: 99%